2017
DOI: 10.1016/j.jcrs.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Visual and refractive outcomes of small-incision lenticule extraction in mild, moderate, and high myopia: Six-month results

Abstract: Small-incision lenticule extraction showed acceptable efficacy, safety, predictability, and stability in low, moderate, and high myopia. The tendency toward undercorrection in the high myopia group suggests the need to modify the nomograms of small-incision lenticule extraction in highly myopic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…In the current study, these correlations were not statistically significant at 2 years. The safety index of 1.05 was comparable to lesser myopia studies ( Table 3), suggesting that LVC in VHM has equivalent safety to that of high myopia [16,25,29,36]. As reported elsewhere [6], the high-rate of microstriae (11.9%) can likely be attributed to the very deep ablations (mean 150 μm), although only two eyes with microstriae were deemed to be visually significant requiring intervention.…”
Section: Complicationssupporting
confidence: 67%
“…In the current study, these correlations were not statistically significant at 2 years. The safety index of 1.05 was comparable to lesser myopia studies ( Table 3), suggesting that LVC in VHM has equivalent safety to that of high myopia [16,25,29,36]. As reported elsewhere [6], the high-rate of microstriae (11.9%) can likely be attributed to the very deep ablations (mean 150 μm), although only two eyes with microstriae were deemed to be visually significant requiring intervention.…”
Section: Complicationssupporting
confidence: 67%
“…Our results are comparable to the previous studies of TransPRK [ 3 , 5 , 7 ] and small-incision lenticule extraction. [ 14 , 15 ] We found a statistically significant difference in postoperative UDVA between the low and moderate myopia groups versus the high myopia group. The reason may be the increased HOAs of the cornea postoperatively or the changes of high myopia fundus preoperatively.…”
Section: Discussionmentioning
confidence: 72%
“…Ikeda T et al [ 17 ] found 77% of high myopic eyes showed no change or gain in CDVA one year after LASIK. Torky MA et al [ 14 ] found that 88.2% of high myopic eyes got the SE within±0.50D by SMILE surgery six months postoperatively. Similarly, Jin HY et al [ 18 ] found that 87% of high myopic eyes got the SE within±0.50D by SMILE surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Sekundo et al [1] first introduced this new procedure in 2011. e first clinical study [2] of femtosecond lenticule extraction in China was also reported in 2011. Numerous clinical studies [3][4][5][6][7][8][9] suggested that SMILE is a safe and effective procedure for myopia correction, and the follow-up periods in these studies mostly spanned from 3 months to 3 years, but rarely up until 4 years [10][11][12][13][14]. In 2019, we [15] have previously compared the 5-year outcomes of SMILE and femtosecond laser-assisted LASIK (FS-LASIK) in patients with myopia.…”
Section: Introductionmentioning
confidence: 99%